Pengaruh Penambahan Nilon Thermoplastik Daur Ulang pada Nilon Thermoplastik Murni terhadap Modulus Elastisitas Basis Gigi Tiruan - Magfira Magfira; Isma Suprapti; Sri Irmayana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The use of thermoplastic nylon denture bases produces waste that causes environmental pollution. To overcome this environmental pollution, the remaining nylon can be recycled into denture bases. The purpose of this study was to determine the effect of adding recycled thermoplastic nylon to pure thermoplastic nylon on the modulus of elasticity of denture bases. The laboratory experiment research method was carried out in the laboratory of the Dental Engineering Study Program D III, Universitas Megarezky, Makassar and the Mechanical Laboratory of the Ujung Pandang State Polytechnic. This study used Thermoplastic Nylon material, in this case using Thermoset material which was divided into 4 sample groups, namely: pure Thermoplastic Nylon (Sample A), a combination of 75% pure Thermoplastic Nylon with 25% recycled Thermoplastic Nylon (Sample B), a combination of 50% pure Thermoplastic Nylon with 50% recycled Thermoplastic Nylon (Sample C), 100% recycled Thermoplastic Nylon (Sample D). The results of the study showed that the modulus of elasticity with an average value for the pure Thermoplastic Nylon group was 832.97 MPa, the 75% pure Thermoplastic Nylon 25% Recycled Thermoplastic Nylon group was 831.29 MPa, the 50% pure Thermoplastic Nylon 50% Recycled Thermoplastic Nylon group was 830.11 Mpa and the highest was the 100% Recycled Thermoplastic Nylon group, which was 851.44 MPa. In conclusion, the addition of recycled thermoplastic nylon to pure thermoplastic nylon can cause changes in the modulus of elasticity in the form of a lack of flexibility of the denture base.